A composite chassis for a formula student vehicle. (2017) - Ferreira, Ricardo; Sousa, Luís; Infante, Virgínia
The present work aims to analyse different types of chassis used in Formula Student vehicles. This analysis is done under the same circumstances for all structures: the suspension lines and packaging of main components are fixed. A value for torsional stiffness is estimated based on the car's handling. A tubular space frame from previous prototype is re-analysed using structural optimisation methods, aiming for weight reduction while considering the new torsional stiffness target. This new arrangement is used as a benchmark with the composite structures. An overview of the used type of composite materials is presented, the equivalency process is explained and a model to identify lay-ups for the different zones is developed. Several arrangements are analysed for the semi-monocoque and monocoque structures, considering vacuum infusion and Prepreg. A local study is developed to define monocoque's pickup inserts points dimensions. A study is performed on bonded joint along the vacuum infusion.